Changes in Metabolic Chemical Reporter Structure Yield a Selective Probe of O-GlcNAc Modification - Chuh, Kelly N. (American Chemical Society, 2014)
[Image: see text] Metabolic chemical reporters (MCRs) of glycosylation are analogues of monosaccharides that contain bioorthogonal functionalities and enable the direct visualization and identification of glycoproteins from living cells. Each MCR was initially thought to report on specific types of glycosylation. We and others have demonstrated that several MCRs are metabolically transformed and enter multiple glycosylation pathways. Therefore, the development of selective MCRs remains a key unmet goal. We demonstrate here that 6-azido-6-deoxy-N-acetyl-glucosamine (6AzGlcNAc) is a specific MCR for O-GlcNAcylated proteins. Biochemical analysis and comparative proteomics with 6AzGlcNAc, N-azidoacetyl-glucosamine (GlcNAz), and N-azidoacetyl-galactosamine (GalNAz) revealed that 6AzGlcNAc exclusively labels intracellular proteins, while GlcNAz and GalNAz are incorporated into a combination of intracellular and extracellular/lumenal glycoproteins. Notably, 6AzGlcNAc cannot be biosynthetically transformed into the corresponding UDP sugar-donor by the canonical salvage-pathway that requires phosphorylation at the 6-hydroxyl. In vitro experiments showed that 6AzGlcNAc can bypass this roadblock through direct phosphorylation of its 1-hydroxyl by the enzyme phosphoacetylglucosamine mutase (AGM1). Taken together, 6AzGlcNAc enables the specific analysis of O-GlcNAcylated proteins, and these results suggest that specific MCRs for other types of glycosylation can be developed. Additionally, our data demonstrate that cells are equipped with a somewhat unappreciated metabolic flexibility with important implications for the biosynthesis of natural and unnatural carbohydrates.